Beauty queen - Mlynowski, Sarah (Mlynowski, Sarah. Whatever after, 2015)
Abby's first problem is that Jonah has lost all his memories of the magic mirror and their adventures, so when they get sucked through into Beauty and the Beast, he is unaware of the danger, and picks one of the Beast's roses--her second problem is locating Beauty and performing a match-making miracle in order to recover her brother, and still make it back to the real world before their parents miss them.